KONSEP LIFELONG EDUCATION DALAM ISLAM DAN PEMAKNAANNYA SEJAK USIA SEKOLAH DASAR - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
This study was conducted to describe the meaning of lifelong education, its existence based on the perspective of Islamic teachings, and its interpretation in elementary schools. In this study, the researcher used a qualitative research method (library research) to elaborate on the concepts and theories of lifelong education. It is widely approved that education is an inherent need that every human being must possess. Lifelong learning is a continuous and never-ending process (continuing learning) from the cradle to the grave. Each developmental phase of an individual is traversed through learning in order to fulfill their developmental tasks; thus, learning begins in infancy/toddlerhood, progresses through childhood (the elementary school years), and continues into adulthood, even until the end of life. Education lasts a lifetime, enriched by experiences gained both inside and outside the school environment. Within Islamic education, this is known as lifelong education. Particularly at the elementary school level—a phase where children begin to think rationally—the introduction of lifelong education should be instilled so that children understand that learning never stops. This indicates that education occurs without boundaries, beginning from birth till death